Explaining recent postictal epilepsy EEG results by the G-lymphatic clearance hypothesis. (April 2020) - Rabinovitch, A.; Aviram, Ira; Biton, Y.; Braunstein, D.
Abstract: Two recent postictal EEG measurements demonstrate somewhat conflicting results of epileptic behavior clearance in different brain parts. Both measurements observed two modes of seizure cessation, an abrupt and a gradual one, with slightly different statistics. No explanations were given for the appearance of these modes. Both measurements differ also in assessing the postictal brain activity or lack thereof, specifically the gamma activity. Using our G-Lymphatic clearance hypothesis, these results can be explained theoretically. The presence of two modes can be related to the order of ISF-CSF cleaning of brain parts. The reduced activity can be ascribed to neuronal ingredients deficiency brought about by the seizure related excess brain activity and by an over cleaning by the G-Lymphatic system.